Dampak Investasi Domestik dan Pengeluaran Publik terhadap Pertumbuhan Ekonomi Nasional - izza, olivia maghfirotul (Maliki Interdisciplinary Journal, 2025)
Economic growth is an important indicator for assessing the progress of a country, which is influenced by various macroeconomic factors. Investment is considered a key driver in boosting productivity and job creation. Labor, as a human resource, plays a central role in production activities, while the level of education reflects the quality of the workforce itself. On the other hand, government expenditure plays a strategic role in providing infrastructure and public services that support economic growth. This study uses secondary time series data obtained from the Central Bureau of Statistics and related institutions over a specific period, employing multiple linear regression analysis to measure the contribution of each variable to GDP as an indicator of economic growth. The analysis results show that investment and education have a positive and significant impact on economic growth. Meanwhile, labor shows an insignificant effect in certain years, indicating the need to improve labor quality not only quantitatively but also in terms of skills and competencies. On the other hand, government spending has a positive but varying impact, depending on the effectiveness of budget allocation and the sectors prioritized.These findings indicate that the government needs to enhance the effectiveness of public spending and the